Long-read single-molecule maps of the functional methylome - Sharim, Hila; Grunwald, Assaf; Gabrieli, Tslil; Michaeli, Yael; Margalit, Sapir; Torchinsky, Dmitry; Arielly, Rani; Nifker, Gil; Juhasz, Matyas; Gularek, Felix; Almalvez, Miguel; Dufault, Brandon; et al. (Genome Research, 2019)
We report on the development of a methylation analysis workflow for optical detection of fluorescent methylation profiles along chromosomal DNA molecules. In combination with Bionano Genomics genome mapping technology, these profiles provide a hybrid genetic/epigenetic genome-wide map composed of DNA molecules spanning hundreds of kilobase pairs. The method provides kilobase pair–scale genomic methylation patterns comparable to whole-genome bisulfite sequencing (WGBS) along genes and regulatory elements. These long single-molecule reads allow for methylation variation calling and analysis of large structural aberrations such as pathogenic macrosatellite arrays not accessible to single-cell second-generation sequencing. The method is applied here to study facioscapulohumeral muscular dystrophy (FSHD), simultaneously recording the haplotype, copy number, and methylation status of the disease-associated, highly repetitive locus on Chromosome 4q.